2005
DOI: 10.1007/s00216-005-0211-6
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a novel method for the analysis of chlorinated pesticides in soils using microwave-assisted extraction–headspace solid phase microextraction and gas chromatography–tandem mass spectrometry

Abstract: A new procedure for determining eleven organo-chlorine pesticides in soils using microwave-assisted ex-traction (MAE) and headspace solid phase microextraction (HS-SPME) is described. The studied pesticides consisted of mirex, α-and γ-chlordane, p,p′-DDT, heptachlor, heptachlor epoxide isomer A, γ-hexachlorocyclohexane, dieldrin, endrin, aldrine and hexachlorobenzene. The HS-SPME was optimized for the most important parameters such as extraction time, sample volume and temperature. The present analytical proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Majority of these methods include adjustment of the ionic strength of solution (Berrada et al, 2004;Beltran et al, 2003;Kin & Huat, 2010;Chai & Tan, 2009;Đurović et al, 2010a, 2010bZhao et al, 2006;Filho et al, 2010;Lambropoulou & Albanis, 2003;Fytianos et al, 2006;Đurović et al, 2009), and some of them adjustment of the pH value (Berrada et al, 2004;Ravelo-Pérez et al, 2008;Parrilla Vázquez et al, 2008;Filho et al, 2010;) prior to SPME analysis. The research results indicate that the most often used SPME fibers in the pesticide residues analysis (PDMS and PA) are a good choice for determination of: phenyl urea in carrot, onion and potato (Berrada et al, 2004); OCPs in soils (Zhao et al, 2006;Herbert et al, 2006); OPPs in strawberries and cherries (Lambropoulou i Albanis, 2003) and samples of banana, apple, grapefruit, orange, lemon, kiwi, pineapple, pear, peach, apricot, grapes, melon, lotus, plum, mango, cherry and coconut (Fytianos et al, 2006); OCPs and OPPs in cucumber and strawberry (Kin & Huat, 2010); pesticides belonging to different chemical groups in tomato and cucumber (Chai & Tan, 2009), mango (Filho et al, 2010), soil (Đurović et al, 2010a, 2010b), i.e. in samples of potato, tomato, onion, cabbage and pepper (Marković et al, 2010).…”
Section: Fig 2 Procedures For Microextraction Of Analytes From Solutionmentioning
confidence: 98%
See 1 more Smart Citation
“…Majority of these methods include adjustment of the ionic strength of solution (Berrada et al, 2004;Beltran et al, 2003;Kin & Huat, 2010;Chai & Tan, 2009;Đurović et al, 2010a, 2010bZhao et al, 2006;Filho et al, 2010;Lambropoulou & Albanis, 2003;Fytianos et al, 2006;Đurović et al, 2009), and some of them adjustment of the pH value (Berrada et al, 2004;Ravelo-Pérez et al, 2008;Parrilla Vázquez et al, 2008;Filho et al, 2010;) prior to SPME analysis. The research results indicate that the most often used SPME fibers in the pesticide residues analysis (PDMS and PA) are a good choice for determination of: phenyl urea in carrot, onion and potato (Berrada et al, 2004); OCPs in soils (Zhao et al, 2006;Herbert et al, 2006); OPPs in strawberries and cherries (Lambropoulou i Albanis, 2003) and samples of banana, apple, grapefruit, orange, lemon, kiwi, pineapple, pear, peach, apricot, grapes, melon, lotus, plum, mango, cherry and coconut (Fytianos et al, 2006); OCPs and OPPs in cucumber and strawberry (Kin & Huat, 2010); pesticides belonging to different chemical groups in tomato and cucumber (Chai & Tan, 2009), mango (Filho et al, 2010), soil (Đurović et al, 2010a, 2010b), i.e. in samples of potato, tomato, onion, cabbage and pepper (Marković et al, 2010).…”
Section: Fig 2 Procedures For Microextraction Of Analytes From Solutionmentioning
confidence: 98%
“…In most cases, SPME method was based on the analysis of sample mixture with water, regardless of whether the extraction medium was placed directly into the formed suspension (Berrada et al, 2004;Beltran et al, 2003;Đurović et al, 2007c, 2010b, or the sampling was done from the gaseous phase (Chai & Tan, 2009;Kin & Huat, 2010;Zhao et al, 2006;Lambropoulou & Albanis, 2003;Fytianos et al, 2006). However, quite a number of researchers opted for methods based on SPME determination of pesticides combined with the extraction of samples with organic solvent or solvent mixture, and the corresponding dilution of extract obtained with water (Wennrich et al, 2001;Ravelo-Pérez et al, 2008;Parrilla Vázquez et al, 2008;Đurović et al, 2007c, 2010a, 2010bHerbert et al, 2006;Vega Moreno et al, 2006). Majority of these methods include adjustment of the ionic strength of solution (Berrada et al, 2004;Beltran et al, 2003;Kin & Huat, 2010;Chai & Tan, 2009;Đurović et al, 2010a, 2010bZhao et al, 2006;Filho et al, 2010;Lambropoulou & Albanis, 2003;Fytianos et al, 2006;Đurović et al, 2009), and some of them adjustment of the pH value (Berrada et al, 2004;Ravelo-Pérez et al, 2008;Parrilla Vázquez et al, 2008;Filho et al, 2010;) prior to SPME analysis.…”
Section: Fig 2 Procedures For Microextraction Of Analytes From Solutionmentioning
confidence: 99%
“…As a few examples, MAE has proven to be suitable for the extraction of polycyclic aromatic hydrocarbons and phenolic compounds (L o opez-Á vila, Young, and Beckert 1994), polychlorinated biphenyls (Herbert et al 2006a) and pesticides (Sun and Lee 2003;Morais, Tavares and Delerue-Matos 2005;Herbert et al 2006b) from several different matrices. Although numerous papers have reported the use of MAE, very few of them refer its application to the extraction of pesticide residues from fresh vegetables.…”
Section: Screening Of Carbamates and Ureas In Fresh And Processed Tommentioning
confidence: 98%
“…Therefore, microwave heating improve SPME sampling efficiency for organic compounds. In recent years, many studies can be found using MA-SPME for analysis of pesticides in various samples 35,36 .…”
Section: Introductionmentioning
confidence: 99%